2023
DOI: 10.1177/14696053231153499
|View full text |Cite
|
Sign up to set email alerts
|

Events, narrative and data: why new chronologies or ethically Bayesian approaches should change how we write archaeology

Abstract: In this paper, we discuss how the history of our discipline continues to shape how we think with material culture to produce narratives. We argue that recent developments in scientific dating—in combination with New Materialist and Big Data approaches—offer the potential to produce radical new interpretations. However, we can only achieve this if we adopt ‘ethically Bayesian’ approaches which recognise that some of the most fundamental aspects of our epistemological structures are highly situated, reflecting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Finally, we come to the study of micromorphology in relation to understanding past events, and the relevance of our soil micromorphological work in, for instance, the Bayesian modelling of radiocarbon dates (e.g. Kleijne and Huisman, 2023b;Gri ths et al, 2023;Bayliss, 2015, 689), where understanding and separating events is critical. Our study has shown that the three chronologically separate events studied here (the formation of the subsoil, the dumping of the shells and the trampling of the shells) are effectively spatially compressed into a single microfacies of "shells within sediment", through the act of trampling.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we come to the study of micromorphology in relation to understanding past events, and the relevance of our soil micromorphological work in, for instance, the Bayesian modelling of radiocarbon dates (e.g. Kleijne and Huisman, 2023b;Gri ths et al, 2023;Bayliss, 2015, 689), where understanding and separating events is critical. Our study has shown that the three chronologically separate events studied here (the formation of the subsoil, the dumping of the shells and the trampling of the shells) are effectively spatially compressed into a single microfacies of "shells within sediment", through the act of trampling.…”
Section: Discussionmentioning
confidence: 99%
“…Research in the Carpathian Basin and Balkans has often been dominated by culture history / typo-chronological frameworks. It is important to avoid slippage between speaking of ceramic groups as material culture categories with spatial and temporal relevance and the people who made the pots [63,64]. Ceramic groups cannot viewed as direct proxies for ethnic or cultural identity and political boundaries, but represent expressions of choice and knowledge [65].…”
Section: Plos Onementioning
confidence: 99%
“…To go beyond periodisations and aim at a trans-chronological megalithism contributes to overpass modernity in Archaeology and their time models, whose usage also poses ethical problems (Griffiths et al, 2023). It also aims at changing linear timelines in Prehistory, where "[…] unrelenting change of the modern era is focused and directional."…”
Section: Introductionmentioning
confidence: 99%